GE_GERICHTE P/9111/2021 vom 3. November 2021 - GE Cour de justice (2021)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);CITATION À COMPARAÎTRE;DÉFAUT(CONTUMACE);NOTIFICATION ÉCRITE | CPP.355.al2; CPP.85.al2; CPP.87.al4; CPP.201